Investigation on The Characteristics of Magnetorheological Elastomer Using Natural Rubber and Petroleum-Based Oil - Mohd Zarir, Marni Zalikha (IRC, 2020)
A comprehensive study on the characteristics of magnetorheological elastomer (MRE) has yet been reported although it is vital prior to employ the MRE in any smart devices. The purpose of this paper therefore is to study the influence of petroleum-based oil (PBO) on the characteristics of MRE using natural rubber as MRE matrix and carbonyl iron particles as magnetizable particles. Three PBO that will be used are naphthenic oil, paraffin oil, and light mineral oil. The compositions were mixed and cured without an applied magnetic field to fabricate isotropic MRE. The fabricated MRE was characterized with respect to magnetic properties, morphology, and thermal behaviour. The results showed that natural rubber-based MRE with light mineral oil had homogeneous dispersion of carbonyl iron particles within the matrix. In the meantime, the MRE with naphthenic oil obtained low retentivity magnetization as a result of carbonyl iron particles as a soft magnetic particles that easily demagnetized.